Why Do Religious Ideas Matter? The Multidimensionality of the Indonesian Public Sphere - Darmini, Asep Muizudin Muhamad (Universitas Islam Internasional Indonesia (UIII), 2024)
In this paper, I challenge the claim of the universalistic public sphere by providing contextual complexity of the national and local public sphere in Indonesia. In the original version of the Habermasian public sphere, people sat together in the salon and the café to exchange their ideas, sustaining the secular, capitalistic, and individualistic public sphere. However, further critics have shown the problems of putting secular ideas as the central force of the public sphere, particularly as it overlooks the complexity of the public sphere in religious contexts. These critics are particularly relevant to understanding the Indonesian public sphere in which the Muslim-majority population aims to dominate public life, as the religiously motivated political agenda has a further consequence for democratisation in Indonesia, which has been heralded as a prime example of harmony between Islamic values and Western democracy. At the same time, digitalisation has facilitated a religious revival in the national public sphere, combining religious sentiment within a highly individualised and digitalised society. This paper analyses the challenges of the digital divide in the local public sphere of pondok pesantren (Indonesian Islamic boarding schools). With a lack of digital access and democratic practices in day-to-day pondok pesantren life, communalistic religious practices have dominated the public sphere of these boarding schools. Within such complexity, this paper deliberates on how the local and national contexts in Indonesia shed light on the multidimensionality of the public sphere.